2D seismic interpretation and hydrocarbon prospects for the Neogene-Quaternary succession in the Temsah Field, offshore Nile Delta Basin, Egypt. (July 2019) - Sarhan, Mohammad Abdelfattah; Safa, Mona Gomaa
Abstract: This study is concerned with the Neogene-Quaternary subsurface sedimentary succession of the Temsah Field in the northeastern offshore Nile Delta Basin. A sequence stratigraphic analysis based on seismic and available well data enables the subdivision of the investigated succession into two megasequences: the Pre- and Post-Messinian Megasequences. The Pre-Messinian Megasequence encompasses Miocene rock units, whereas the Post-Messinian Megasequence includes Pliocene-Pleistocene rock units. The detailed sequence stratigraphic analysis presented herein subdivides the Pre-Messinian Megasequence into three 3 rd -order depositional sequences as follows (from the base to the top): Sequence-1 (Serravallian Sidi Salim Formation), Sequence-2 (Tortonian Wakar Formation), and Sequence-3 (Messinian Rosetta Formation). The Post-Messinian Megasequence is also subdivided into three additional 3 rd -order seismic sequences: Sequence-4 (Lower-Middle Pliocene Kafr El-Sheikh Formation), Sequence-5 (Late Pliocene El-Wastani Formation) and Sequence-6 (Pleistocene Mit Ghamr Formation). This study suggests that the sea level underwent six transgressive-regressive depositional cycles during the evolution of the Neogene-Quaternary succession. The greatest relative sea level fall occurred during the Messinian, while the highest identified relative sea level rise occurred during the Lower-Middle Pliocene. The interpreted NW-SE anticline represents a distinctive four-way closure that may form a suitable structural hydrocarbon trap within the sandy intervals of the siliciclastic Sidi Salim and Wakar Formations in the Temsah Field. Moreover, the identified single and multiple buried channels within the Kafr El-Sheikh Formation are recommended for further exploration and possible drilling. Highlights: Sequence stratigraphiy for the Neogene-Quaternary section in Nile Delta Basin. Relative sea level curve during Neogene-Quaternary time span in Nile Delta Basin. Hydrocarbon prospects for Neogene sequence in offshore Nile Delta Basin.